Association between exposure to tobacco information through mass media, smoking households and secondhand smoke exposure in adolescents: Survey data from South Korea - Wenbin Du; Gaoran Chen; Minmin Gu; Huixin Deng; Won G. Choi (Tobacco Induced Diseases)
Introduction To explore the current situation of exposure of Korean adolescents to secondhand smoke (SHS) in households our study aimed to determine the relationship between family member smoking status, exposure to tobacco information through mass media, and household SHS exposure.